2006
DOI: 10.1142/s0217984906011517
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Chemically Synthesized Doped Poly(o-Anisidine) and Copoly{aniline-(O-Anisidine)}

Abstract: Substituted polyaniline poly(o-anisidine) and copoly{aniline-(o-anisidine)} were synthesized by the oxidative chemical polymerization method. Sulfuric acid was used as the dopant during the polymerization process. Synthesized polymers were subjected to the spectroscopic, X-ray and thermal analysis. Formation of different oxidation states of the polymer were confirmed by the spectroscopic (UV-VIS and FTIR) analysis. Polymers reveal polycrystalline nature and orthorhombic crystal structure. Three step decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…A unique shoulder is observed in all the copolymers at 405, 415, 440 nm and 402, 412, 405 nm which is due to polaron-p transition [18]. The observed absorption bands are in well agreement with the reported literatures [18][19][20][21][22][23].…”
Section: Uv-vis and Ftir Spectroscopic Measurementssupporting
confidence: 90%
“…A unique shoulder is observed in all the copolymers at 405, 415, 440 nm and 402, 412, 405 nm which is due to polaron-p transition [18]. The observed absorption bands are in well agreement with the reported literatures [18][19][20][21][22][23].…”
Section: Uv-vis and Ftir Spectroscopic Measurementssupporting
confidence: 90%
“…UV‐VIS spectroscopy is a powerful tool for the elucidation of the interactions between the solvent, the dopant and the polymer chains . Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition of polymers is controllable by variation of some parameters, such as applied potential, monomer concentration, substituted monomers, and changing electrolyte solution [7,8]. Among the polymers, composites of polyaniline (PANI) have attracted enormous interest due to their unique properties [9][10][11][12][13][14]. For instance, Mottaghitalab et al [15] reported that PANI/CNTs composites exhibited improved mechanical strength and conductivity.…”
Section: Introductionmentioning
confidence: 99%